A Study on Energy Efficiency of a 3 Storey Office Building in Senai Airport City Johor - Batcha, Teo Kok Swee; Sulastri Sabudin; Mohideen Batcha, Mohd Faizal (Journal of Advanced Mechanical Engineering Applications, 2026)
The Malaysian government is prioritizing energy efficiency to address rising global energy consumption and greenhouse gas emissions. Office buildings are significant energy consumers due to various factors such as building design, operational needs and occupancy rate. The Energy Efficiency and Conservation Act (EECA) and the Green Building Index (GBI) are designed to reduce energy intensity and promote environmental goals. Incentives for renewable energy use, such as Net Energy Metering (NEM) program, streamline the sale of surplus solar energy to utility firm like Tenaga National Berhad (TNB). The Sustainable Energy Development Authority (SEDA) advocates for NET Zero Energy Buildings (NZEB) to promote sustainable development and mitigate environmental impact. This study seeks to examines the energy consumption profile of a 3 storey office building in Senai, Johor, identify opportunities for energy saving, aims to improve electrical energy efficiency. The energy efficiency solutions included roof insulation, LED lighting, a multi-split variable refrigerant flow (VRF) air condioning system, precise control of temperature setting, enhanced energy efficiency, and the incorporation of solar energy system is essential in lowering building energy intensity (BEI) significantly. By employing these measures, office building can decrease electricity usage, minimize operation expenses, and mitigate carbon footprint emissions.